A Load Balancing Per Connection Classifier Dengan Pengukuran Quality of Service Pada Jaringan LAN Lingkup Universitas - Aulia Desy Aulia Nur Utomo (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
Abstract In the use of internet networks that are general in nature need to implement an appropriate network configuration to maximize the use of internet connections provided by service providers. This is important for the optimal use of internet services and in accordance with utilities that are basically general and shared can be achieved. Per Connection Classifier is a load balancing method for distributing traffic loads to more than one network connection point in a balanced way, so that traffic can run optimally. This research focuses on network configuration methods to maximize internet usage for all users. Quality of Service is used to see the performance of network traffic which is indicated by the value of the parameter delay, throughput, and packet loss. Based on the results of testing and research that have been carried out before and after using load balancing per connection clasifier, the delay value is decreased from 180.26 ms to 148.36 ms and throughput increased from 1.76% to 2.03%, then packet loss decreased from 25.37% to 18.59% according to the TIPHON standard. Keywords: Quality of Service, Per Connection Classification, load balancing, delay, throughput, packet loss